Defining road service to facilitate road infrastructure asset management. Issue 4 (11th September 2019) - Adey, Bryan T; Burkhalter, Marcel; Martani, Claudio
Abstract : Road infrastructure asset management requires making decisions that affect how infrastructure provides service – for example, the intervention strategies to follow for specific assets, the intervention programmes to implement for entire networks and the way for interventions to be executed once it is decided that they should be executed. These decisions should be made to maximise the net benefit of infrastructure for all stakeholders and be made consistently and transparently. Currently, the definitions of service used by road infrastructure asset managers either are incomplete or are built on combinations of metrics, which give an idea of service but do not measure service directly. Neither allows for consistent and transparent decision-making that leads to the maximisation of the net benefit for all stakeholders. In this paper, a definition of the service provided by road infrastructure is provided that enables consistent and transparent decisions to maximise the net benefit for all road infrastructure stakeholders. The service definition is used to determine the net-benefit-maximising intervention strategy that shows its usefulness and its ability to let stakeholders see how they will be affected by decisions and that all of their concerns have been adequately taken into consideration when decisions are made.